2021
DOI: 10.9734/ca/2021/v10i230165
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASC Score as a Predictor of Coronary Artery Disease: A Cross Sectional Observational Study

Abstract: Background: The CHA2Ds2-VASC was was revealed to be a predictor for thromboembolism event in patients who do not have atrial fibrillation or who have supra ventricular arrhythmia. The aim of this work was to evaluate the role of CHA2DS2 – VASC score in prediction of coronary artery disease. Methods: This cross sectional observational study included 150 patients underwent coronary angiography for diagnosis and treatment of CAD. There were 59 patients with ACS (including STEMI and Non-STEMI) and 91 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…As regards the score of the current study patients was ranging from 0 to 4. Similarly, Shehata et al (17) in a previously conducted study found that CHADs-VASc score among acute coronary syndrome was 3.39 (SD 1.22).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As regards the score of the current study patients was ranging from 0 to 4. Similarly, Shehata et al (17) in a previously conducted study found that CHADs-VASc score among acute coronary syndrome was 3.39 (SD 1.22).…”
Section: Discussionmentioning
confidence: 67%
“…In this study, 45.0% of the patients was hypertensives. Meanwhile, compared with normal blood pressure, the risk of MI increased with AHA hypertension stage in both sexes and was consistently higher among women than men in many studies (16,17) . The difference is that the present study had male predominance, with no control group included to determine whether hypertension is a risk factor or not.…”
Section: Discussionmentioning
confidence: 96%